2023
DOI: 10.1029/2022jb025681
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Low‐Velocity Belt in the Shallow Anninghe Fault Zone in SW China and Its Implications for Seismotectonics and Earthquake Hazard Assessment

Abstract: The Anninghe fault forms the eastern boundary of the Sichuan‐Yunnan block in Southwest China and has been identified as an earthquake gap zone. This study intends to construct the upper crustal shear wave velocity (Vs) structure beneath the Anninghe fault to understand its seismotectonics and potential large earthquake hazards. We deployed a dense seismic array along the southern central Anninghe fault valley. From the 3‐month continuous records, we calculated vertical‐component cross‐correlation functions (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This feature, also identified as a clear low-resistance zone by Hu et al (2014), aligns with our observations near linear array 04. Luo et al (2023) reported a similar feature beneath the Anninghe fault zone in SW China, interpreted as a water-bearing fracture zone. Considering these findings, we propose that the low-velocity belt beneath the AQ-JX fault could be indicative of a fracture zone.…”
Section: Tectonic Implication Of Inversion Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This feature, also identified as a clear low-resistance zone by Hu et al (2014), aligns with our observations near linear array 04. Luo et al (2023) reported a similar feature beneath the Anninghe fault zone in SW China, interpreted as a water-bearing fracture zone. Considering these findings, we propose that the low-velocity belt beneath the AQ-JX fault could be indicative of a fracture zone.…”
Section: Tectonic Implication Of Inversion Resultsmentioning
confidence: 92%
“…Luo et al. (2023) reported a similar feature beneath the Anninghe fault zone in SW China, interpreted as a water‐bearing fracture zone. Considering these findings, we propose that the low‐velocity belt beneath the AQ‐JX fault could be indicative of a fracture zone.…”
Section: Discussionmentioning
confidence: 93%
“…Earthquakes do not occur everywhere. Fault geometry and the physical properties of fault zones (namely, seismogenic structure), geological and tectonic settings (Wang et al, 2014;Dascher-Cousineau et al, 2020;Gong et al, 2020), as well as crustal movement and the geodynamic environment, play pivotal roles in the seismic patterns (e.g., King, 1978;Ikeda, 2009;Luo et al, 2023). A variety of geophysical and geochemical observations, ranging from ground-related deformation patterns (GPS, SAR, etc.)…”
mentioning
confidence: 99%
“…A variety of geophysical and geochemical observations, ranging from ground-related deformation patterns (GPS, SAR, etc.) (Bürgmann et al, 2000;Zhao et al, 2020) to pre-earthquake changes (geochemical, electromagnetic, hydro-geological, geodetic, or thermodynamic) (Huang F. Q. et al, 2017;Zhou et al, 2020;Chen et al, 2021;Martinelli et al, 2021;Zhou et al, 2021), recorded by ground-based (Li et al, 2022) or satellite-based techniques (Li et al, 2020) may be related to stress variations in the lithosphere (Luo et al, 2023) prior to an eventual large earthquake (Zhao et al, 2022). Even though much effort has been invested, the earthquake "elephant in the room" is still in the process of being understood.…”
mentioning
confidence: 99%